Effect of the target temperature during magnetron sputtering of Nickel. (January 2018) - Caillard, A.; El'Mokh, M.; Lecas, T.; Thomann, A.-L.
Abstract: By disconnecting a nickel target from a water-cooled magnetron, thereby inducing a rise in the target temperature, the time evolution of the cathode voltage and of the magnetic field above the target was measured using a small Hall-effect sensor, enabling the ferromagnetic – paramagnetic transition of the Ni target to be clearly identified. A heat flux sensor was implemented in the high vacuum chamber to measure the energy transferred to the substrate, especially the energy contribution coming from the infrared radiation emitted by the heated target. By coupling the heat flux and the Hall sensors, this study shows that the emissivity and the temperature of the target surface can be determined. A temperature up to 720 ± 30 °C and an emissivity of 0.4 ± 0.02 were obtained for a specific power density of 5 W cm −2 applied on the target. Nickel thin films were deposited on silicon at low and high temperatures (target respectively connected to and disconnected from the magnetron). It was found that the increase in the target temperature leads to an increase in the deposition rate (15% enhancement in the present conditions) and a change in the Ni thin film microstructure (toward a dense and compact columnar structure). Highlights: In a plasma sputtering process called High Temperature Magnetron Sputtering (HiTeMS), the magnetic transition of a Ni target at the Curie temperature (358°C) was unambiguously highlighted and the IR radiation emitted from the target, its emissivity and its surface temperature was measured by coupling magnetic field, cathode voltage and energy flux density measurements. Working with a hot Ni target improves the average deposition rate (15% enhancement in the present conditions).